Perception of green roof and flat roof development in high rise buildings in Malaysia: pros and cons - Abd Razak, Nur Syazanna Iryani; Balasbaneh, Ali Tighnavard (Penerbit UTHM, 2022)
The environmental impact of construction activities occurs from the initial work stages to the construction period, operational period, and the final demolition when a building comes to the end of its life. In order to make sure the construction activity can be run in line with considering the environmental health, green roofs are very relevant to Malaysia which is now experiencing rapid urbanization and loss of green areas in most of its major cities. On the other hand, flat roofs have a wide application in many countries, following the architectural evolution, the emergence of new materials, and the improvement in the performance of the existing ones. This study focuses on the perception of building industry players in the green and flat roofs development in Malaysia’s high-rise building. A questionnaire was distributed to the local building sector in order to fulfill the objectives of the study which are to identify the advantages and disadvantages of green and flat roofs that concern the construction practitioners, to analyze the barriers of the green roof development, and to provide strategies to enhance the implementation of green roof in Malaysia’s construction industry. At the end of the study, green roofs seemed able to offer healing environments but has a limited of roofing materials, skilled labors and professional team required, high consideration of structure, and high installation and construction initial cost.